Neuroprotection of Total Steroid Saponins from Dioscorea zingiberensis against Transient Focal Cerebral Ischemia-Reperfusion Injury in Rats via Anti-Inflammatory and Antiapoptotic Effects - Zhang, Xin-xin; Chen, Lin; Liu, Jian-li; Ito, Yoichiro; He, Jiao; Sun, Wen-ji (Planta Medica, 2014)
Total steroid saponins isolated from Dioscorea zingiberensis have shown a variety of beneficial bioactivities. However, there are no reports about their neuroprotective effects, until now. Therefore, in the present study, we explored the neuroprotective effects of the total steroid saponins from D. zingiberensis on rats against transient focal cerebral ischemia-reperfusion and their underlying mechanisms. Healthy adult Sprague-Dawley rats were randomly assigned to six groups. After pretreatment with D. zingiberensis total steroid saponins intragastrically for six days, the rats were subjected to an ischemia injury by surgery on the middle cerebral artery occlusion for 90 min. Compared to the ischemia-reperfusion group, the D. zingiberensis total steroid saponin group of rats, especially those given a 30-mg/kg dose, showed not only a marked reduction in neurological deficit scores, cerebral infarct volume, and brain edema, but also an increase in neuron survival (Nissl bodies) in the hippocampal cornuammons 1 and cortex hemisphere of the ipsilateral ischemia. At the same time, the inflammatory cytokines in serum induced by the middle cerebral artery occlusion were significantly decreased by the preadministration of D. zingiberensis total steroid saponins. Furthermore, the increase of caspase-3 was evidently reduced in the hippocampal cornuammons 1 and cortex of the hemisphere injured brain. Finally, the downregulating antiapoptotic Bcl-2 and upregulating proapoptotic Bax proteins were obviously suppressed. Taken together, the current findings suggest that D. zingiberensis total steroid saponins played a potential neuroprotective role against a severe injury induced by transient focal cerebral ischemic reperfusion in a rat experimental model, and this role may be mediated by its anti-inflammatory and antiapoptotic actions.
Keywords: Dioscorea zingiberensis; Dioscoreaceae; cerebral ischemia-reperfusion; middle cerebral artery occlusion (MCAO); total steroid saponins; anti-inflammatory; anti-apoptotic